Innovative Approaches in Tracheal Resection and Anastomosis Surgery: Integrating Extracorporeal Membrane Oxygenation for Enhanced Safety - Son, Joohyung; Son, Bong Soo; Park, Jong Myung; Cho, Jeong Su; Kim, Yeongdae; I, Hoseok; Kim, Do Hyung (Yonsei medical journal, 2025)
Tracheal resection with end-to-end anastomosis (TREE) has many advantages over conservative treatment in terms of long-term results; however, this method requires improved safety and accessibility. We aimed to combine expanded venovenous extracorporeal membrane oxygenation (ECMO) during TREE surgery. Between May 2006 and December 2022, 41 patients diagnosed with tracheal stenosis or tracheal tumors underwent TREE. The non-ECMO and ECMO groups were classified based on the presence or absence of intraoperative ECMO support. Reconstruction length was slightly longer in the ECMO group than in the non-ECMO group, but there was no statistical significance ( =0.082). There was no significant difference between the two groups in terms of operative time ( =0.698), estimated blood loss ( =0.210), and duration of mechanical ventilation ( =0.713). There was a significant difference in intensive care unit stay between the two groups ( =0.013) due to the postoperative maintenance of ECMO. There were no cases of early mortality in either group during hospitalization ( >0.999). ECMO support could assist in more challenging cases as it makes surgery easier in difficult patient scenarios.